The meanings of Chinese slangs in Kazakh language (Journal of Oriental Studies, 2017)
Today, we have so many internet users, including social network users.As we all know, there are no young people who are not familiar with jargonsand slangs, which are used by us almost every single day. Slang consistsof a lexicon of non- standard words and phrases in a given language.Jargon is a type of language that is used in a particular context and may notbe well understood outside of it. The use of jargons and slangs is not onlypopular among younger in Kazakhstan, but also in China. However, theuse of Network Catchwords seems evenmore frequent in China.